Microscopic study of the Sn132,124+Zr96 reactions: Dynamic excitation energy, energy-dependent heavy-ion potential, and capture cross section - Oberacker, V. E.; Umar, A. S.; Maruhn, J. A.; Reinhard, Paul-Gerhard (Physical Review C - Nuclear Physics, 2010)
We study reactions between neutron-rich Sn132 nucleus and Zr96 within a dynamic microscopic theory at energies in the vicinity of the ion-ion potential barrier peak, and we compare the properties to those of the stable system Sn124+Zr96. The calculations are carried out on a three-dimensional lattice using the density-constrained time-dependent Hartree-Fock method. In particular, we calculate the dynamic excitation energy E*(t) during the initial stages of the collision. The barrier heights and widths of the heavy-ion potential increase substantially with Ec.m. energy. The capture cross sections for the two reactions are of similar magnitude, but the interaction barrier for the neutron-rich system is found to be significantly (9 MeV) lower. A comparison with recently measured data is given. © 2010 The American Physical Society.
CRIS-Team Scopus Importer:2023-07-24